Mapping the Interactions Between Hummingbirds and Plants in a Region of the Colombian Andes (Early view) - Juliana Karime Astudillo Ortíz, Jorge Mario Becoche-Mosquera and Luis Germán Gómez-Bernal, (Tropical Life Sciences Research, 2026)
Pollination is a key ecological process that ensures plant reproduction and supports the stability and biodiversity of natural ecosystems. In high Andean environments, hummingbirds act as essential pollinators due to their physiological adaptations that allow them to forage in extreme climatic conditions and at high elevations. However, the ongoing transformation of these ecosystems driven by deforestation, land-use change, and climate variability highlights the urgent need to understand the structure and resilience of pollination networks. In this study, we analyzed the interaction network between hummingbirds and ornithophilous plants in a remnant of Andean forest in southwestern Colombia. Interactions were documented through trail surveys, focal observations, and mist-netting over a three-year sampling period. We recorded 269 interactions between 10 hummingbird species and 28 plant species, achieving 95% sampling completeness. Network analysis revealed low specialization, intermediate modularity, and a predominance of generalist species, suggesting a relatively cohesive but potentially vulnerable system. These findings contribute valuable empirical evidence on how mutualistic interactions are structured in tropical montane forests and highlight the importance of preserving not only species richness but also the ecological interactions that sustain ecosystem function. This knowledge is essential for designing conservation and restoration strategies that enhance the resilience of high mountain ecosystems in the face of current and emerging threats.